Growth Mechanism of Cubic-Silicon Carbide Nanowires. (11th February 2010) - Cheong, K. Y.; Lockman, Z.
Abstract : Cubic-SiC nanowires were synthesized using activated carbon powder and Si substrate in vacuum at 1200–1350 ∘ C for 1–4 hours. The nanowires were grown according to the following proposed mechanisms: (1) diffusion of C/CO into Si substrate, (2) weakening of Si bond and atomic kick-out, (3) formation of Si-C in vapor phase, (4) formation of saturated SiC layer, (5) formation of pyramid-like SiC nanostructure, and (6) formation of SiC nanowires.